2017
DOI: 10.1016/j.jlp.2017.03.009
|View full text |Cite
|
Sign up to set email alerts
|

Propagation of a confined explosion to an external cloud

Abstract: Since the pioneering work of Harrison and Eyre (1986), the existence of secondary or external explosion outside explosion vents is recognized. It was later shown (Proust, 2004(Proust, , 2010) that the phenomenon is rather systematic and that this explosion can be much more powerful than the internal explosion particularly when the mixture is very reactive. But today, the understanding of the formation of the external cloud and its subsequent combustion remains largely outstanding. Very rapid burning was notice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…Gao et al, 3,4 Tascón et al, 5 and Yan and Yu 6 focused on the influence of different static activation overpressures on the venting overpressure within the vessel using traditional venting techniques. In addition, the influence of the vent area has been extensively studied 7‐9 . Tascón et al 10‐12 also confirmed above influencing factors (static activation overpressure and vent area) by numerical simulations with FLACS‐Dust Ex software.…”
Section: Introductionmentioning
confidence: 85%
“…Gao et al, 3,4 Tascón et al, 5 and Yan and Yu 6 focused on the influence of different static activation overpressures on the venting overpressure within the vessel using traditional venting techniques. In addition, the influence of the vent area has been extensively studied 7‐9 . Tascón et al 10‐12 also confirmed above influencing factors (static activation overpressure and vent area) by numerical simulations with FLACS‐Dust Ex software.…”
Section: Introductionmentioning
confidence: 85%
“…Results obtained by Proust et al 24 showed that a jet flame occurs under conditions of rear ignition in the case of a small vent area similar to that in the current study (Figure 2(a)). However, no mushroom-like flame was observed at the vent area of 0.16 m 2 , which was also obtained by Jeŕome et al, 27 because a small vent area permits only a slower gas-venting rate so that the combustion rate in the chamber exceeds the venting rate during venting. 5 Therefore, the internal pressure in a high-pressure state after opening the vent causes a continuous and rapid discharged velocity, moving the vented gas away from the vent.…”
Section: Effect Of Vent Areasmentioning
confidence: 99%
“…The largest length of jet flames is closely linked to the hydrogen equivalence ratio. Jérôme et al 27 clarified the fact that, in the case where the discharge area is sufficiently small, the external vortex bubble formed by the ejection is disturbed to form a jet flame. By measuring the speeds of laminar flames of a methane–air mixture in a bomb of a constant volume and shock tube, Hu et al 28 found that a faster laminar flame speed of the methane-rich mixture was measured using the linear approach compared with that predicted using a nonlinear approach.…”
Section: Introductionmentioning
confidence: 99%